2022
DOI: 10.1186/s42523-022-00177-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal dynamics of the bovine udder microbiota

Abstract: Background In recent years, the number of studies concerning microbiota of the intramammary environment has increased rapidly due to the development of high-throughput sequencing technologies that allow mapping of microbiota without culturing. This has revealed that an environment previously thought to be sterile in fact harbours a microbial community. Since this discovery, many studies have investigated the microbiota of different parts of the udder in various conditions. However, few studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The four cows included in this project were defined as H-cows (SCC > 100,000 cells/mL) or L-cows (SCC < 100,000 cells/mL) based on a previous study conducted by Winther et al where the SCC were measured over three consecutive days at the start of the project [ 4 ]. The study revealed a difference in the stability and composition of the udder microbiota between H- and L-cows, where the H-cows displayed an imbalanced microbiota and a lower diversity over time compared to the L-cows.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The four cows included in this project were defined as H-cows (SCC > 100,000 cells/mL) or L-cows (SCC < 100,000 cells/mL) based on a previous study conducted by Winther et al where the SCC were measured over three consecutive days at the start of the project [ 4 ]. The study revealed a difference in the stability and composition of the udder microbiota between H- and L-cows, where the H-cows displayed an imbalanced microbiota and a lower diversity over time compared to the L-cows.…”
Section: Resultsmentioning
confidence: 99%
“…One sample, JT24, contained blood. As no imbalance in the microbiota was detected in this sample, which is usually the case during a bacterial infection [ 3 , 4 ], the blood could be a result of a yeast infection or trauma to the udder [ 39 ].
Figure 1 Microbial composition of the 32 milk samples based on 16 S amplicon sequencing .
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid advancement of high-throughput next-generation sequencing (NGS) technology and bioinformatics pipelines, culture-independent techniques have exponentially grown in use over the last few years to overcome some inherent limitations of cultivation methods ( 8 , 9 ). This has become evident due to the increased number of studies concerning the bovine milk microbiome, especially based on targeted approaches such as metataxonomic analyses ( 10 13 ).…”
Section: Introductionmentioning
confidence: 99%